Distributional effects of FDI: How the interaction of FDI and economic policy affects poor households in Bolivia - Peter Nunnenkamp; Rainer Schweickert; Manfred Wiebelt (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2006)
This paper provides a computable general equilibrium analysis of the medium to long-run impact of FDI inflows on poverty and income distribution in Bolivia. The simulation results suggest that FDI inflows enhance economic growth and reduce poverty. However, the income distribution typically becomes more unequal. In particular, FDI widens income disparities between urban and rural areas. The Bolivian government may promote growth-enhancing and poverty-alleviating effects of FDI by overcoming labour market segmentation and providing complementary public investment in infrastructure. Yet, simulated policy reforms or alternative productivity scenarios are hardly effective in reducing the divide between urban and rural areas.
Keywords: O5; C68; D3; F21; 330; Poverty and income distribution; Bolivia; Computable general equilibrium analysis; Foreign direct investment; Direktinvestition; Wirtschaftspolitische Wirkungsanalyse; Armut; Einkommensverteilung; Stadt-Land-Beziehung; Allgemeines Gleichgewicht; Schätzung; Bolivien